Results from the fertilizer demonstration experiment with maize at Farm for the Future Tanzania in Iringa, in 2021: Final narrative report - Mtakwa, Peter W.; Urio, Ndelilio A.; Mtakwa, Alpha P.; Brentrup, Frank; Tibezukwa, George; Loon, Marloes P. van; Hijbeek, Renske; ten Berge, Hein F.M.; Ittersum, Martin K. van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In 2021, an experiment was run for the fourth consecutive season at the Farm for the Future Tanzania Ltd (FFF) which is part of Ilula Orphan Program (IOP)’s Farm, Ilula, Iringa Region, in Tanzania. The FFF farm, is training farmers in 16 villages, with a focus on dissemination activities at regional, as well as national level. The purpose of the experiment is to experimentally test and demonstrate low-emission crop fertilisation strategies that combine high maize yields with high nutrient use efficiency and low emissions. Four nutrient management treatments were combined in a full factorial setup with two tillage options. Lowest yields were obtained with no fertilizer addition (control treatment) under conventional tillage and reduced tillage (1-2 t/ha), while the treatments with fertilizer addition consistently showed very high yields (close to 10 t/ha). Root number and root length were larger for reduced tillage compared to conventional tillage at the control treatment, but this difference was not significant. Root penetration resistance was significantly higher at conventional tillage compared to reduced tillage for the control treatment. Around 100 pupils from primary as well as secondary school made two field visits to the trial. Also, a farmers field day was organized, and from the sixteen villages surrounding the farm, a total of about 400 farmers attended the planting session and the field day.